Initial emergency response performance of fire fighters in Malaysia - Subramaniam, Chandrakantan; Ali, Hassan; Mohd Shamsudin, Faridahwati (Emerald Group Publishing Limited, 2012)
Purpose– The purpose of this paper is to identify the initial emergency response time of fire fighting teams in Malaysia. Design/methodology/approach– In an emergency incident time is of the essence, and the basic philosophy of an emergency response agency is to respond as quickly as possible to minimize the loss of life and property damage. In the current study, emergency response performance refers to team members’ speed in responding to emergency situations, which was measured as the time taken for the team members to get to the fire truck from the waiting room in selected fire stations in Malaysia.The data collection period lasted for five months. Findings – This study found that the overall average initial emergency response time was 84 seconds, while the overall average weighted initial emergency response time was 3.71 seconds per meter.The current study has demonstrated that the average initial emergency response performed by fire fighting teams in Malaysia is apparently better than that reported by previous studies by other emergency responders.Originality/value – This paper presents empirical evidence of the initial emergency response time of fire fighters in Malaysia, by taking into account the distance traveled by the responders. As such, the performance measure obtained gives a meaningful indicator.The finding of the current study is then compared to emergency response performance by other emergency response agencies in other countries.